Noise-induced cochlear synaptopathy in C57BL/6 N mice as a function of trauma strength: ribbons are more vulnerable than postsynapses - Blum, Kerstin; Schepsky, Pauline; Derleder, Philip; Schätzle, Philipp; Nasri, Fahmi; Fischer, Philipp; Engel, Jutta; Kurt, Simone (Frontiers in Cellular Neuroscience, 2024)
Noise-induced cochlear synaptopathy is characterized by irreversible loss of synapses between inner hair cells (IHCs) and spiral ganglion neurons (SGNs) despite normal hearing thresholds. We analyzed hearing performance and cochlear structure in C57BL/6 N mice exposed to 100, 106, or 112 dB SPL broadband noise (8–16 kHz) for 2 h. Auditory brainstem responses (ABRs) were assessed before, directly after, and up to 28 days post-trauma. Finally, the number, size, and pairing of IHC presynaptic (CtBP2-positive) ribbons and postsynaptic AMPA receptor scaffold (Homer1-positive) clusters were analyzed along the cochlea. Four weeks after the 100 dB SPL trauma, a permanent threshold shift (PTS) was observed at 45 kHz, which after the higher traumata extended toward middle to low frequencies. Loss in ABR wave I amplitudes scaled with trauma strength indicating loss of functional IHC synaptic connections. Latencies of wave I mostly increased with trauma strength. No trauma-related OHC loss was found. The number of synaptic pairs was reduced in the midbasal and basal cochlear region in all trauma conditions, with ribbon loss amounting up to 46% of control. Ribbons surviving the trauma were paired, whereas 4–6 unpaired postsynapses/IHC were found in the medial, midbasal, and basal regions irrespective of trauma strength, contrasting findings in CBA/CaJ mice. Our data confirm the susceptibility of ribbon synapses and ABR wave I amplitudes to a noise trauma of 100 dB SPL or larger. Notably, peripheral dendrites bearing IHC postsynapses were less vulnerable than presynaptic ribbons in C57BL/6 N mice.